Global Instability
IX, 239 p.
Keywords: Global Instability: Uncertainty and New Visions in Political Economy presents a series of papers that address the political consequences of globalization for states and their populations, while exploring the issue of alternatives to the model of globalization we are presently experiencing. The focus moves from the world of international agreements to the national and sub-national dilemmas that are posed by attempting to manage a set of global developments within a given territory. The initial chapter, by Daniel Drache, explores a still-born post-war international organization, the International Trade Organization, that offers a different vision of how a globally integrated economy might operate. A number of papers then explore the challenges posed by today's globalization, including currency instability in an environment of financial deregulation, the rights conferred on investors by the North American Free Trade Agreement, and the progressive liberalization of trade in services built into the General Agreement on Trade in Services.